Hellenizing art in ancient Nubia, 300 BC-AD 250, and its Egyptian model s a study in "acculturation" - Török, László, 1941- (Culture and History of the Ancient Near East, 2011)
Presenting a large body of evidence for the first time, this book offers a comprehensive treatment of Nubian architecture, sculpture, and minor arts in the period between 300 BC-AD 250. It focuses primarily on the Nubian response to the traditional pharaonic, Hellenistic/Roman, Hellenizing, and "hybrid" elements of Ptolemaic and Roman Egyptian culture. The author begins with a history of Nubian art and a critical survey of the literature on Ptolemaic and Roman Egyptian art. Special chapters are then devoted to the discussion of the Egyptian-Greek interaction in the arts of Ptolemaic Egypt, the place of Egyptian Hellenistic and Hellenizing art within the oikumene, the pluralistic visual world of Ptolemaic and Roman Egypt, as well as on the specific genre of terracotta sculpture. Utilizing examples from Meroe City and Musawwarat es Sufra, the author argues that cultural transfer from Ptolemaic and Roman Egypt to Nubia resulted in an inward-focused adaptation. Therefore, the resulting Nubian art from this period expresses only those aspects of Egyptian and Greek art that are compatible with indigenous Nubian goals.